Resiliensi Kinerja Keuangan Pt Waskita Karya (Persero) Tbk - Serlin Serang, Firman, Tuti Fitriani, Mahfudnurnajamuddin (Program Pascasarjana STIE Amkop Makassar, 2023)
PT Waskita Karya (Persero) Tbk. It continues to increase from year to year, while the condition of net profit at PT Waskita Karya (Persero) Tbk. experienced a very significant decline in profit. Meanwhile, the condition of Total Current Assets at PT Waskita Karya (Persero) Tbk. Experiencing Fluctuations. Meanwhile, regarding income conditions at PT Waskita Karya (Persero) Tbk. Experiencing a very significant decline, the aim of this research is to find out and analyze how well the financial performance of PT WASKITA KARYA (PERSERO) TBK. In measuring the company's financial performance, the data analysis technique used is the financial liquidity ratio which includes the Current Ratio and profitability ratio which includes the net profit margin, the research method uses descriptive analysis and the One Sample t Test with the help of SPSS version 20. The sample used is purposive sampling is a technique for determining certain considerations. With the criteria (1) the latest data for 10 consecutive years, namely 2012-2021 (2) availability of data that can be accessed by the author, (3) 10 year sample data already represents existing population data for research needs. Based on the results of research and analysis, it shows that the company's financial performance at PT WASKITA KARYA (PERSERO) TBK. Judging from the liquidity ratio analysis, Current Racio is considered to be performing poorly and in terms of the profitability ratio analysis, Net Profit Margin is considered to be performing well. Keywords: Analysis of liquidity ratios and profitability ratios